Interfaces de una plataforma de generación de aplicaciones de flujo de trabajo de procesos administrativos en la ESPAM MFL - Cevallos Molina, Karla Estefania (2017)
The realization of this thesis was carried out with the objective of developing the interfaces of the workflow application generation platform for the optimization of the administrative processes in the ESPAM MFL, obtaining a total integration of the processes and a systematized control of the fulfillment of the same, through the technology Workflow. The MEIDAW methodology was applied, which provides the necessary guidelines for the development of Workflow systems. It has two phases, the first one defined the general aspects of the process and the second the development of the product as such. We used the BPMN 2.0 standard that defines the set of graphical elements for the design of business process diagrams; the main tools used for the development of the interfaces were: the Visual Studio 2013 programming IDE, the MVC software architecture pattern, the Razor view engine with HTML5 and CSS3, as well as the C #, JavaScript and XML languages. In order to establish the functional requirements of the system, the authors designed UML use case diagrams, which define the functional structure of the system from the point of view of the user. The results obtained through the automation of the process "PRD-ERS-001" can conclude that through the interfaces it facilitates the automation of the processes, checking the hypothesis.